Factors associated with early outcomes following standardised therapy in children with ulcerative colitis (PROTECT): a multicentre inception cohort study. (December 2017) - Hyams, Jeffrey S; Davis, Sonia; Mack, David R; Boyle, Brendan; Griffiths, Anne M; LeLeiko, Neal S; Sauer, Cary G; Keljo, David J; Markowitz, James; Baker, Susan S; Rosh, Joel; Baldassano, Robert N; et al.
Summary: Background: Previous retrospective studies of paediatric ulcerative colitis have had limited ability to describe disease progression and identify predictors of treatment response. In this study, we aimed to identify characteristics associated with outcomes following standardised therapy after initial diagnosis. Methods: The PROTECT multicentre inception cohort study was based at 29 centres in the USA and Canada and included paediatric patients aged 4–17 years who were newly diagnosed with ulcerative colitis. Guided by the Pediatric Ulcerative Colitis Activity Index (PUCAI), patients received initial standardised treatment with mesalazine (PUCAI 10–30) oral corticosteroids (PUCAI 35–60), or intravenous corticosteroids (PUCAI ≥65). The key outcomes for this analysis were week 12 corticosteroid-free remission, defined as PUCAI less than 10 and taking only mesalazine, and treatment escalation during the 12 study weeks to anti-tumour necrosis factor α (TNFα) agents, immunomodulators, or colectomy among those initially treated with intravenous corticosteroids. We identified independent predictors of outcome through multivariable logistic regression using a per-protocol approach. This study is registered withClinicalTrials.gov, numberNCT01536535 . Findings: Patients were recruited between July 10, 2012, and April 21, 2015. 428 children initiated mesalazine (n=136), oral corticosteroids (n=144), or intravenous corticosteroids (n=148). Initial mean PUCAI was 31·1 (SD 13·3) in children initiating with mesalazine, 50·4 (13·8) in those initiating oral corticosteroids, and 66·9 (13·7) in those initiating intravenous corticosteroids (p<0·0001 for between-group comparison). Week 12 outcome data were available for 132 patients who initiated with mesalazine, 141 with oral corticosteroids, and 143 with intravenous corticosteroids. Corticosteroid-free remission with the patient receiving mesalazine treatment only at 12 weeks was achieved by 64 (48%) patients in the mesalazine group, 47 (33%) in the oral corticosteroid group, and 30 (21%) in the intravenous corticosteroid group (p<0·0001). Treatment escalation was required by nine (7%) patients in the mesalazine group, 21 (15%) in the oral corticosteroid group, and 52 (36%) in the intravenous corticosteroid group (p<0·0001). Eight patients, all of whom were initially treated with intravenous corticosteroids, underwent colectomy. Predictors of week 12 corticosteroid-free remission were baseline PUCAI less than 35 (odds ratio 2·44, 95% CI 1·41–4·22; p=0·0015), higher baseline albumin by 1 g/dL increments among children younger than 12 years (4·05, 1·90–8·64; p=0·00030), and week 4 remission (6·26, 3·79–10·35; p<0·0001). Predictors of treatment escalation by week 12 in patients initially treated with intravenous corticosteroids included baseline total Mayo score of 11 or higher (2·59, 0·93–7·21; p=0·068 [retained in model due to clinical relevance]), rectal biopsy eosinophil count less than or equal to 32 cells per high power field (4·55, 1·62–12·78; p=0·0040), rectal biopsy surface villiform changes (3·05, 1·09–8·56; p=0·034), and not achieving week 4 remission (30·28, 6·36–144·20; p<0·0001). Interpretation: Our findings provide guidelines to assess the response of children newly diagnosed with ulcerative colitis to standardised initial therapy and identify predictors of treatment response and failure. These data suggest that additional therapeutic interventions might be warranted to improve early outcomes, especially in patients presenting with severe disease and requiring intravenous corticosteroids. Funding: National Institutes of Health.